Hospital efficiency and consultants' private practices: Analysing the impact of a voluntary reform - Xidong Guo (University College Dublin, UCD School of Economics, 2023)
This paper explores the effectiveness of the voluntary reform. It studies a voluntary healthcare reform that was implemented in Ireland in 2008. The analysis is conducted using a theoretical model and empirical evidence. In 2008, in the hope to reduce waiting lists, new contracts were issued which limited the proportion of private patients that consultants could treat while and compensating them with a higher fixed salary. This new contract was optional for consultants hired before 2008. It was compulsory for newly hired consultants. The theoretical model establishes that this reform reduced the overall number of treated patients because the restriction on private practices disincentivises consultants to attend to more patients. A difference-in-differences approach is then employed where inpatients entering through the Emergency Department are considered as the control group. I use micro-level data to access the impact on the Length of Stay (LOS) and control patients' characteristics and medication conditions. Using Little' Law, I establish that the LOS is negatively correlated with the number of admissions. The empirical results also show a 0.28-day increase in the LOS for public patients, which suggests that the 2008 voluntary contract reform led to unexpected adverse impacts and may fail to address the waiting list issue
Keywords: I18; I10; H44; J41; 330; private practice; consultant’ s contract; length of stay; voluntary reform